COMPARATIVE EVALUATION OF THE CRESTAL BONE LEVEL AROUND DENTAL IMPLANTS PLACED IN ONE STAGE AND TWO STAGE SURGICAL APPROACHES: A CLINICO-RADIOGRAPHIC STUDY (Journal of Pharmaceutical Negative Results, 2023)
Background: It is general consensus that maintenance of bone around dental implants is one of the most important features in long term success of the implant and over the decades attempts are being made to reduce the amount of crestal bone loss around the implants placed so as to increase the longevity of the dental implants. One such method is the placement of two piece implant in one stage surgery thus, avoiding the need of second surgical procedure and allowing uninterrupted healing of the peri- implant tissue.Aim: The study plan to evaluate the crestal bone level around dental implants placed through one-stage and two-stage surgical approaches.Materials and Methods: A prospective randomized, comparative, single blind split mouth study was designed in which twenty 2-piece implants were placed in the posterior mandibular area of ten systemically healthy patients following either two- stage (Group I) or one-stage (Group II) surgical approaches. The crestal bone level was assessed radiographically, at implant placement, at 3 months post implant placement, while implant loading and after 3 and 6 months of implant loading.Results: The difference in the crestal bone loss around dental implants placed in one- stage and two-stage surgical approaches was statistically insignificant.Conclusion: One-stage approach for implant placement may be as promising as two- stage surgical approach. Thus, to reduce the treatment period and provide earlier esthetics without undergoing second stage surgical intervention the surgeons can insert implants through one-stage approach.